# Solve for b 5b(3b-5)=0 5b(3b-5)=0
Divide each term in 5b(3b-5)=0 by 5.
5b(3b-5)5=05
Cancel the common factor of 5.
Cancel the common factor.
5b(3b-5)5=05
Divide b(3b-5) by 1.
b(3b-5)=05
b(3b-5)=05
Divide 0 by 5.
b(3b-5)=0
If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.
b=0
3b-5=0
Set the first factor equal to 0.
b=0
Set the next factor equal to 0 and solve.
Set the next factor equal to 0.
3b-5=0
Add 5 to both sides of the equation.
3b=5
Divide each term by 3 and simplify.
Divide each term in 3b=5 by 3.
3b3=53
Cancel the common factor of 3.
Cancel the common factor.
3b3=53
Divide b by 1.
b=53
b=53
b=53
b=53
The final solution is all the values that make 5b(3b-5)5=05 true.
b=0,53
The result can be shown in multiple forms.
Exact Form:
b=0,53
Decimal Form:
b=0,1.6‾
Mixed Number Form:
b=0,123
Solve for b 5b(3b-5)=0

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top